Carcass traits of different marketable sizes of rohu, Labeo rohita (Hamilton, 1822). (26th November 2012) - Sahu, B. B.; Samal, R.; Meher, P. K.; Das, P. C.; Mishra, B.; Sahu, A. K.; Jayasankar, P.
Summary The present study was carried out to investigate the carcass traits of farmed freshwater Labeo rohita in relation to body size as important information to calculate yield and/or support for machine/manual processing. For this purpose ninety specimens were collected for nine weight groups from 600 to 1100 g, each group with a 100 g increment. Specimens were collected from grow‐out culture ponds of the Central Institute of Freshwater Aquaculture (CIFA), Bhubaneswar. The carcass evaluation technique was followed to evaluate carcass yield, offal yield and carcass cutability. Head size percentage of rohu increased as the body mass increased, which in turn increased the processing yield. Dry matter and ether extract percentage also increased with the body mass; however, moisture percentage showed a decreasing trend. The fore cut showed a distinctly higher ether extract percentage followed by the middle and posterior cuts. There was a good correlation development to describe the relationship between yield traits and body weight.